PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL SERTA DAMPAKNYA PADA KUALITAS LAYANAN (STUDI PADA RUMAH SAKIT REFERRAL MAUBESSI, TIMOR LESTE) - Antonnio de Sousa, Evelio (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this research is to determine the effect of leadership on organizational commitment, work motivation against the influence of organizational commitment, the influence of organizational commitment to quality of service, leadership influence on the quality of service, and the influence of motivation on the quality of service. The results of testing the hypothesis (H1) proves that leadership and significant positive effect on organizational commitment is proven true. Means the better the leadership, the organizational commitment will also be better. The results of testing the hypothesis (H2) prove that there is the influence of motivation on organizational commitment proved to be correct. The higher motivation the higher the organizational commitment. The results of testing the hypothesis (H3) prove that there is a positive effect of and organizational commitment to quality service is proved to be correct. The better the Organizational Commitment, then the better the quality of hospital services. The results of testing the hypothesis (H4) prove that there is a positive influence on the quality of leadership and service indeed proved true. The better the leadership, then the better the quality of hospital services.